Nuevos datos sobre Hypostomus commersoni (Siluriformes: loricariidae) anómalo en la Laguna Chascomús (Buenos Aires, Argentina) - Nadalin, Diego O. (2008)
An anomalous specimen of Hypostomus commersoni was captured in «laguna» Chascomús, in August, 2005. This specimen presents a shortening of the craneal region with reduction of the dorsal – lateral plates of the head, reflecting a marked loss of the symmetry. The rest of the body does not show evident modifications.